The Challenges Native Advertising Poses: Exploring Potential Federal Trade Commission Responses and Identifying Research Needs. (January 2019) - Campbell, Colin; Grimm, Pamela E.
Native advertising is a new form of online advertising that appears in many settings, such as blogs, social media, and entertainment and news publications. Native ads typically blend with their surrounding context, stem from sources or placements that do not signal advertising, lack overtly persuasive or sales-focused messaging, and have less clear material outcomes. Such characteristics raise ethical concerns because native ads are more difficult for consumers to identify and because they challenge concepts that are central to current deceptive advertising policy. Native advertising is a Federal Trade Commission enforcement priority, and the agency has developed guidelines for this new ad form. However, the unique characteristics of native advertising likely require novel approaches to protect consumers. In this article, the authors trace the evolution of regulation relevant to native advertising. They identify shortcomings and propose remedies that the Federal Trade Commission or industry could adopt to prevent consumer harm, detect infractions, and enforce its regulations. The authors also develop an agenda for future research needed to more fully inform public policy and industry response in this arena.